Scripting Computer-Supported Collaborative Learning
XXII, 344 p.
Keywords: Research on Computer-Supported Collaborative Learning (CSCL) is a multidisciplinary field located at the intersection of cognitive psychology, computer science, and education. Yet, the different epistemological and theoretical backgrounds of these disciplines often make fruitful exchange between them difficult. CSCL urgently needs to develop and use boundary concepts that can bring these fields closer together to improve cumulative research and development of computer-supported learning environments. Scripting Computer-Supported Collaborative Learning focuses on one term with the potential to become a real boundary concept in CSCL—"scripting". Scripting Computer-Supported Collaborative Learning, which has collected advanced script approaches, demonstrates the opportunities for using synergy to apply the script concept between perspectives and interdisciplinary CSCL approaches to scripting. This volume represents the state of the art of research on scripting computer-supported collaborative learning and provides a starting point for the development of a common understanding of scripting in CSCL. Research on collaboration scripts has an extraordinary potential for advancing the multidisciplinary endeavor of CSCL research and this book provides a rich basis for further exploring and realizing this potential. As such, it will be a valuable resource for research, development, and teaching.